VKCFD2 – from clinical phenotype to molecular mechanism - Czogalla, K. J.; Watzka, M.; Oldenburg, J. (Hämostaseologie, 2016)
Vitamin K 2,3-epoxide reductase complex, subunit 1 (VKORC1) is an enzyme essential for the vitamin K cycle. VKORC1 catalyses the reduction of vitamin K 2,3-epoxide to the quinone form of vitamin K and further to vitamin K hydroquinone. The generated vitamin K hydroquinone serves as substrate for the enzyme γ-glutamyl-carboxylase which modifies all vitamin K-dependent proteins, allowing them to bind calcium ions necessary for physiological activity. Vitamin K-dependent proteins include the coagulation factors FII, FVII, FIX, FX, and proteins C, S und Z. Insufficient VKORC1 enzyme activity results in deficiency of the vitamin K-dependent clotting factors leading to haemorrhagic disorders. This phenotype is known as vitamin K clotting factor deficiency type 2 (VKCFD2). Worldwide, only four families of independent origin have been reported with this rare bleeding disorder. Affected family members carry the mutation VKORC1:p.Arg98Trp in homozygous form, the only mutation found so far to be associated with VKCFD2. Now, ten years after the identification of the VKORC1 gene, the molecular pathomechanism of VKCFD2 has been clarified. The Arg98Trp mutation disrupts an ER retention motif of VKORC1 leading to mislocalisation of the protein to outside the endoplasmatic reticulum. In this review, we summarize the clinical data, diagnosis, therapy and molecular patho -mechanism of VKCFD2.
Keywords: VKCFD2; VKOR; VKORC1; vitamin K; mutation